Book Reviews / Rezensionen - Peter Spahn; Till van Treeck; Bernd Berghuber; Torsten Niechoj; Christoph Scherrer; Stefan Ederer; Jan-Oliver Menz; Lena Vogel (Intervention. European Journal of Economics and Economic Policies, 2008)
Books reviewed: Davidson, Paul (2007): John Maynard Keynes, London/New York Godley, Wynne / Lavoie, Marc (2007): Monetary Economics. An Integrated Approach to Credit, Money, Income, Production and Wealth, Houndmills et al. McCombie, John / Rodriguez Gonzales, Carlos (eds.)(2007): The European Union. Current Problems and Prospects, Basingstoke Priddat, Birger P. (Hg.): Neuroökonomie. Neue Theorien zu Konsum, Marketing und emotionalem Verhalten in der Ökonomie Young, Brigitte (Hg.) (2007): Die politische Ökonomie des Dienstleistungsabkommens (GATS). Gender in EU und China, Baden Baden Reviews of Conference Books of the Research Network Makroeconomics and Macroeconomic Policies / Rezensionen der Tagungsbände des Forschungsnetzwerks Makroökonomie und Makropolitik Hein, Eckhard / Priewe, Jan / Truger, Achim (eds.) (2007): European Integration in Crisis, Marburg Hein, Eckhard / Heise, Arne / Truger, Achim (eds.) (2006): European Economic Policies. Alternatives to Orthodox Analysis and Policy Concepts, Marburg Arestis, Philip / Hein, Eckhard / Le Heron, Edwin (eds.) (2007): Aspects of Modern Monetary and Macroeconomic Policies, Houndsmills et al. Hein, Eckhard / Truger, Achim (eds.) (2007): Money, Distribution and Economic Policy. Alternatives to Orthodox Macroeconomics, Cheltenham et al.
Keywords: 330